The efficacy and safety of treatments for infantile hemangiomas: a Bayesian network meta‐analysis. (14th July 2020) - Yang, Hao; Hu, Dong‐Lai; Xuan, Xiao‐Xiao; Chen, Jun‐Jie; Xu, Sheng; Wu, Xiang‐Jie; Zhang, Hang; Shu, Qiang; Guo, Xiao‐Dong
Abstract: Whether infantile hemangiomas (IHs) need to be treated and which treatment should be preferred are still controversial. We aimed to compare and rank the treatments and identify the optimal treatment for IHs. We searched PubMed, EMBASE, the Cochrane Library, Web of Science, and other sources for randomized controlled trials up to August 2019. We included trials comparingdifferent treatments and reported response or adverse events rate in IH patients. Two reviewers independently evaluated studies by specific criteria and extracted data. We assessed the risk of bias with the Cochrane risk of bias tool. Random‐effects were performed for pair‐to‐pair and Bayesian framework network meta‐analyses. The primary outcomes were efficacy and safety. We deemed 20 studies eligible, including 1149 participants and eight interventions. For efficacy, oral propranolol and topical propranolol/timolol were better than observation/placebo (OR, 95% CrI: 17.05, 4.02–94.94; 9.72, 1.91–59.08). For safety, topical propranolol/timolol was significantly better tolerated than oral propranolol (0.05, 0.001–0.66). Cluster analysis demonstrated oral propranolol was the most effective treatment for IHs, while topical propranolol/timolol showed high efficacy and the highest safety. Laser, intralesional propranolol or glucocorticoid, oral glucocorticoid, or captopril had significantly lower priority than oral propranolol or topical propranolol/timolol considering both efficacy and safety. The quality of evidence was rated as moderate or low in most comparisons. This network meta‐analysis found topical beta‐blockers had the potential to be the most preferable and beneficial option for IHs in consideration of both efficacy and safety.